Impacts of eucalyptus biochar application on greenhouse gas emission from an upland rice–sugarcane cropping system on sandy soil. (27th July 2022) - Butphu, Sucharat; Kaewpradit, Wanwipa
Summary: An on-farm field experiment was conducted in northeastern Thailand to assess the effects of different eucalyptus biochar (BC) application rates, in combination with mineral fertilizers, on upland rice and a succeeding crop of sugarcane on sandy soil. Soil mineral N and greenhouse gas emissions were also evaluated. The field experiment consisted of three treatments: no biochar (BC0), 3.1 Mg ha −1 of biochar (BC1), and 6.2 Mg ha −1 of biochar (BC2). All treatments received the same recommended fertilizer rate. Soil mineral N, and emissions of carbon dioxide (CO2 ), methane (CH4 ), and nitrous oxide (N2 O) were monitored after BC application. The results revealed that the BC2 treatment caused lower soil mineral N content than that of the BC0 treatment during the upland rice period. During the sugarcane period, the BC2 treatment induced a greater soil mineral N content than the BC1 treatment but had no significant difference from the BC0 treatment. The BC2 treatment resulted in significantly lower cumulative CH4 and N2 O emissions than the BC0 treatment during the upland rice period. In conclusion, we found that the BC2 treatment alleviated the global warming potential from CH4 and N2 O emissions throughout the experiment, causing slight changes in soil N availability in the upland rice–sugarcane cropping system.